Receptive breadth and depth of vocabulary knowledge as predictor variables of MUET reading comprehension performance of Malaysian matriculation students - Chee, Yeenny Fong Yeun (2016)
This study aims to investigate whether Malaysian pre-university students’ vocabulary breadth or depth is significantly correlated to their MUET (Malaysia University English Test) reading comprehension scores and to determine a vocabulary breadth threshold level that can assist the learners in comprehending MUET reading component. This is motivated by the issues of less than 7% of candidates managed to obtain Band 5 and 6 in MUET reading component from March 2012 to Nov 2014 and inadequacy of vocabulary which has been repeatedly pointed out by researchers and educators as one of the factors in the unsatisfactory performance of students in their exams. The possibility that lack of vocabulary knowledge may ultimately lead to poor MUET Reading Comprehension results lends credence to the investigation of relationship between learners’ vocabulary knowledge and MUET Reading Comprehension. There is still no research on whether breadth or depth of vocabulary knowledge is related to the MUET reading comprehension component among matriculation students, although there have been many studies that investigated how L2 Malaysian learners’ vocabulary knowledge can be improved (e.g. Chang, 2011; Kanthimathi & Tan, 2012; Naginder Kaur, 2013b; Ng & Sheila, 2011; Prema & Rycker, 2012; Rafiah, 2008). The sample comprised of 225 matriculation students who had taken the MUET. They sat for Read’s Word Associates Test (WAT) Version 4.0 (Read, 1993, 1998) in order to determine their depth of vocabulary knowledge; and Vocabulary Size Test (VST) (Nation & Beglar, 2007) which assessed their breadth of vocabulary knowledge. These test batteries were administered to all the students in one session during their free period in Matriculation College. The findings revealed that: 1) vocabulary breadth itself played a critical role in predicting reading comprehension ability even after controlling for their depth of vocabulary knowledge; 2) compared to vocabulary depth, vocabulary breadth played a relatively more important role in predicting reading comprehension as indicated by the standardised beta value of 0.92; and 3) learners’ vocabulary breadth of 7000 might be sufficient to assist them to score above average (i.e. 56) in the MUET reading comprehension component and this view of threshold is perceived as “probabilistic boundary”. Implications can be drawn from the findings for the Malaysian pre-university ESL classroom in terms of whether vocabulary knowledge is an effective decision-making tool to determine the students’ band in reading to prepare them for the MUET.